EFFECT OF TECHNOLOGICAL ENVIRONMENT ON THE PERFORMANCE OF PUBLIC ENTERPRISES: EVIDENCE FROM ENUGU STATE HOUSING DEVELOPMENT CORPORATION (ESHDC), ENUGU SOUTH-EAST NIGERIA - Ozioko, Helen Nnedinso (African Journal of Social and Behavioural Sciences, 2021)
This study investigates the effect of technological environment on the administrative performance of public enterprises in Nigeria: Evidence from the Enugu State Housing Development Corporation (ESHDC), Enugu, southeast Nigeria. This study adopted descriptive survey research in which a pre-tested and well-validated questionnaire was used to collect data from respondents who were selected from all the staff of the Enugu State Housing Development Corporation (ESHDC) under investigation. The population of the corporation was 875 and from this population, a sample of 268 was drawn using Cochran’s finite population correction factor technique. The questionnaire comprised 15 closed-ended items set on the 5-point Likert-type scale. Results of the reliability test of the questionnaire showed it has a Cronbach’sAlpa index of 0.84. The respondents were selected using purposive sampling method, which allowed selection of only the senior management staff of the parastatal who had good knowledge of the issues concerning technological environment of their organization. Descriptive statistics that consists of frequency, counts, tables and percentages was used to analyze the data as Multiple Regression Analysis was used in testing the hypotheses of the study. Both the analysis and tests were done with the aid of SPSS software. The findings of this study reviewed that technological invention and innovation have significant effect on the profit margin of ESHDC, Enugu; that automation has significant effect on the sales growth of ESHDC, Enugu; and that technological changes have significant effect on the number of beneficiaries of houses constructed by ESHDC, Enugu. The study recommended that manufacturing firms particularly public owned construction firms in Nigeria should always strive to align with the trend and pace of technological inventions and innovation in society. Again, the study also recommended that publicly owned enterprises, particularly those in the construction sub-sector should address the two problems of lack of funds and poor technical know-how among their employees which are prevalent in Nigeria. Finally, the study also advised the government to address the issue of poor power supply currently ravaging the Nigerian business environment, as no technology however sophisticated or readily available can produce the desired effect without adequate energy supply upon which it depends.